A new species of Campsurus (Ephemeroptera: Polymitarcyidae: Campsurinae) from Argentina and Uruguay and redescription of C. evanidus and C. jorgenseni with new synonymies - Emmerich, Daniel; Molineri, Carlos (Zootaxa, 2011)
The subfamily Campsurinae (Ephemeroptera: Polymitarcyidae) includes one of the most specious genera of Ephemeroptera, Campsurus (with 40 known species), with a Pan-American distribution and its greatest diversity in South America. The following new synonymies are proposed: C. evanidus Needham & Murphy, 1924 (=C. juradinus Navás, 1930) and C. jorgenseni Esben-Petersen, 1912 (=C. scutellaris Needham & Murphy, 1924). Redescriptions, drawings and photographs are provided for both species. C. vulturorum sp. nov. from Argentina and Uruguay is described and illustrated for all life stages. It is characterized, in the adult stage, by: very large size (male fore wings 15.9–20.5 mm, female fore wings 21.0–28.0 mm), posterior margin of male abdominal sternum IX convex and rounded, pedestals subrectangular with a short projection on outer-posterior margin; penes widely separated distally, each arm formed by two lobes; and in mature nymphs by: mandibular tusks robust with a large submedian tubercle and six subapical rounded and small tubercles, maxilla with a short flat and triangular membranous gill on cardo.